Is There any Commitment for Oral and Dental Health Promotion in Iran? - Khoshnevisan, Mohammad H. (Journal of Dental School, 2024)
Despite oral health reform introduced by the Ministry of Health and Medical Education, not much oral health improvement has been reported so far. The dmft index in 6 year old children has been steadily increasing since 1998 when the first national oral health survey was conducted in Iran. The dmft index for primary dentition was 4.8 in 1377 (1998); 5 in 1383 (2004); 5.16 in 1391 (2012) and 5.84 in 1395 (2016) national survey. Without timely attention to primary dentition, permanent teeth will be affected during the mixed dentition period and if not attended early enough, tooth loss would be the inevitable consequence. Local national data shows that over 52 percent of our elderly population are completely edentulous. Aside from these local effects in the oral cavity, there are ample evidence on the association of oral and systemic conditions. Meaning that, oral diseases may cause or intensify systemic diseases such as stroke, cardiovascular, respiratory, urinary, and digestive system; as well as low birth weight and premature birth in pregnant ladies. The good news is that all these problems are preventable because oral diseases are preventable. Based on 2012 national data, only 12% of 5-6 year old children were caries-free meaning that dental caries is a silent epidemy in Iran. According to this data 27.4% of the 12 year old children were caries-free. However, after laps of 3 years when these children are 15, only 0.4% of them are caries-free! New caries development in this 27% of children, clearly shows our collective failure in oral health promotion strategies. But why and for how long more we should witness such a tragedy despite having all the necessary means to tackle this problem. When comparing our country to many other developing countries, we are very happy to have an oral health system in Iran, but unfortunately this system doesn’t work properly, because it does not have a proper leadership and structure. There are dental and oral health units in different departments, working independently like isolated islands without any coordination with each other. For the same reason there is no coordination between prevention, treatment, education, research and dental equipment departments. That’s why we do not implement a nationwide policy for oral health promotion and we do not have a leadership to plan, coordinate and improve the oral health of the nation according to appropriate evidence-based strategies. Although, we are living under resistive economy, many decision makers do not pay any attention to low cost preventive dentistry for improving the nation’s oral health, rather follow the costly and wrong remedy suggestions. Increasing the number of dental schools, increasing the number of dental students without considering the current shortcomings of dental schools are just a few to mention. There is no report of oral health improvement by increasing the number of dentist or dental schools. While, spending the cost of one dental school on prevention, promotion and maintenance of community oral health could help a lot. Based on local investigations, developing an oral health structure at the national level is the first priority (1-3) in order to unify all dental and oral health related units located in different departments, in order to follow a single national oral health policy and strategy. Another important priority is manpower development plan with special attention to national prevention activities. If called on local Dental Public Health experts, they can provide a well-defined comprehensive national oral health plan. Although, under current situation we are going to miss the 2025 (1404) health system national objectives, but we can plan for definitely having caries-free generation in a 12-year period if proper oral structure is approved by the Ministry of Health and Medical Education in Iran. Although, a single country is the focus of discussion in this commentary, sharing of the information may be useful for other developing nations as well.